(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The aim of the research is to identify the level of psychological hardness of a sample of swimmers in Damascus Governorate. Differences in the level of psychological hardness between the members of the research sample are defined according to the sex variables (males / females) and age (12/13/14/15) years. The sample consisted of (77) individuals divided into (54) males and (23) females. They were selected in a random stratified manner, where they applied a measure of psychological rigidity (prepared by the researcher) after verifying of validity and reliability. The results indicated that: 1. There is an average level of psychological hardness in general among swimmers and members of the research sample in Damascus Governorate. 2. There are statistically significant differences between the mean scores of the research sample on the psychological hardness scale according to gender variable in favor of males 3. There are statistically significant differences between the mean scores of the individuals on the psychological rigidity scale according to the age variable for the benefit of the larger age.